(untitled) (Research, Society and Development, 2021)
This article aims to present the experience of the group “Trilhas”, conducted as an intervention during the discipline “Estágio Específico em Psicologia e Saúde” at the Federal University of Paraná. The group was developed at a Centro de Atenção Psicossocial in the state of Paraná and aimed to identify the patients therapeutic itineraries, that is, the paths taken by de patients during the search for attention for their health conditions and promote greater levels of autonomy in their future paths. The group’s proposal was divided into three parts: “life story”, “the intersectorial network” and “building the support network” which constituted the seventeen weekly meetings. The group allowed the participants to think about their life stories and to identify the services that answer their health needs.The importance of the group as an instrument that enhances development Sewas observed, providing the development of skills and potential that were previously denied to the participants. In addition, the group owes the mental health service users a reflection on their life stories, identity and foster the development of new interests in sports, culture, education and recreation activities within their neighborhood or community, seeking to expand their routine outside the CAPS.